Sistem Informasi E-Proposal Kegiatan Kemahasiswaan (Studi Kasus: STMIK Amik Riau) - Junadhi Junadhi (RJOCS (Riau Journal of Computer Science), 2019)
Proposal is a condition that must be fulfilled in making an activity. An activity cannot work if the proposal is not approved or without a proposal. The effectiveness of proposal management greatly influences the running of an activity. If the acceptance of the proposal is still by binding and sent to the recipient's room and the examination of the old proposal will hamper the implementation of an activity. Therefore making the proposal management system better, more effective and more efficient will help the activities themselves. This system offers online based using the PHP programming language, and MySQL database. The process of the e-proposal system involves student organizations, student affairs, and administrators as actors of the e-proposal system. The e-proposal system provides a system of submission, examination up to filing activity proposals, and a tracking system that makes it easier for student organizations to monitor the proposal. Overall the e-proposal system makes the performance of each part involved effective. Effective performance will make proposal management more efficient